Drug safety sciences and the bottleneck in drug development - Watkins, P B (Clinical pharmacology and therapeutics, 2011)
During a recent review of a new drug application for treatment of a chronic disease, US Food and Drug Administration (FDA) regulators agreed with the sponsor's assessment of efficacy. However, it was noted that two subjects receiving active treatment experienced abnormal liver chemistries that possibly, but not definitely, indicated a liver safety liability. The sponsor was told that a prerequisite for approval would be a new clinical trial involving 20,000 patients treated for 1 year, with 10,000 receiving the new drug and 10,000 receiving a comparator treatment. The sponsor is now faced with the substantial costs involved in undertaking such a large study, the loss of patent life during the conduct and analysis of the study, and the prospect of losing in-class market position. If the drug is ultimately approved, this detour will result in costs and potential revenue loss to the sponsor of well over $1 billion.